The Competitiveness of Qatari Tourism: A Comparative and SWOT Analysis - Yap, Ghialy; Saha, Shrabani; Alsowaidi, Saif S. (Advances in Social Sciences Research Journal, 2022)
Purpose- Qatar has placed its tourism sector as one of the main strategies of economic diversification to achieve sustainable tourism goal. The country aims to develop diverse tourism products, ranging from cultural, urban, and nature tourism to education. The government has invested a huge amount in designing and building tourism infrastructures such as the eight new stadiums to host the 2022 World Cup, the national museum, Museum of Islamic Art, Katara Cultural Village, Souq Waqif, and many resorts and high end hotels. Given these significant tourism investments, it is unquestionable that the country reaps commensurate long-term benefits in terms of growth of its tourism sector and possible ripple effects in other sectors of the economy. Hence, this study reconnoitres the viability of positioning Qatar’s tourism sector as being pivotal to its economic-diversification strategy by comparing its tourism competitiveness with its strong competitors, namely the United Arab Emirates, Egypt, Saudi Arabia and Turkey. Methodology- To examine this, the study employs secondary data, questionnaire surveys as well as SWOT analysis to identify the strengths and weaknesses of Qatar relative to the competing destinations. Findings- The findings reveal that Qatar is not price competitive with the nearby countries. Furthermore, the competing nations, in general, have longer and deeper expertise in tourism, and invested more resources than Qatar in developing their tourism sectors. However, Qatar performed the best for its health and financial systems, compared to its competitors, based on scheme of the Global Competitiveness Rankings. In order to increase its tourism, the country should focus more on developing the highest quality of health tourism products and targeting on wealthy tourists who can afford to buy a property and live in Qatar as second-home residents. Originality/value- This paper investigates the tourism competitiveness of Qatar in comparison of its neighbouring destinations with respect to the goals set up by the Qatari government. Based upon the analysis, it can be concluded that Qatar has loss its price competitiveness to its neighbouring countries. Furthermore, the study provides a comprehensive examination of Qatar and its competitors using all indices provided by the Travel and Tourism Competitiveness reports, and conduct strengths and weaknesses analysis based on these indicators.